Paraguayan Parents’ Supernatural Beliefs on Causes of Birth Defects - Çaksen, Hüseyin (International Journal of Human and Health Sciences (IJHHS), 2025)
Abstract not available International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 134-135